Impact of self‐monitoring of salt intake by salt meter in hypertensive patients: A randomized controlled trial (SMAL‐SALT). Issue 10 (12th September 2021) - Wiriyatanakorn, Sirichai; Mukdadilok, Anucha; Kantachuvesiri, Surasak; Mekhora, Chusana; Yingchoncharoen, Teerapat
Abstract: Salt intake over reference level would result in elevated blood pressure (BP) and long‐term morbidity. Salt meter is a device used to detect sodium content in daily food. This study aimed to evaluate the efficacy of salt‐meter addition to dietary education. The authors conducted a randomized‐controlled trial in hypertensive patients with uncontrolled BP (systolic BP ≥140 mmHg or diastolic BP ≥90 mmHg). Patients were randomized to receive salt meter plus dietary education (group A) or education only (group B), and followed up for 8 weeks. The primary endpoint was change in 24‐h urinary sodium excretion. Changes in BP, salt taste sensitivity, cardio‐ankle vascular index (CAVI) were also analyzed. There were total number of 90 patients who had complete follow‐up, 45 in each group. Mean age was 62.9 years and 53% were females. Mean baseline 24‐h urine sodium was 151.6 mmol/24 h and mean SBP and DBP were 152.8 and 83.4 mmHg, respectively. Baseline characteristics were similar between two groups. At 8 weeks, mean change in urine sodium were –31.83 mmol/24 h and 0.36 mmol/24 h in group A and group B, respectively ( p  = .006). Mean decrease in BP were SBP, 14.44 versus 8.22 mmHg ( p  = .030), and DBP 5.53 versus 1.93 mmHg ( p  = .032). The salt sensitivity was improved more in group A. There was no different between change in CAVI. From this study, salt meter in conjunction with dietary education, for self‐monitoring of salt intake is superior to education alone in hypertensive patients, and provided better blood pressure control. Salt meter should be considered in uncontrolled hypertensive patients.